Pengaruh Pendapatan Asli Daerah, Dana Perimbangan, dan Pertumbuhan Ekonomi terhadap Kinerja Keuangan Daerah - Syafelina, Muharisa; Arza, Fefri Indra (Universitas Negeri Padang, 2025)
This study aims to examine the effect of local own-source revenue, balance funds, and economic growth on the financial performance of local governments. This research employs a quantitative approach. The sample was selected using a total sampling technique, consisting of 190 local government observations in West Sumatra Province during the 2014–2023 period. Data were analyzed using panel data analysis with EViews 12. The results indicate that local own-source revenue and economic growth have a positive and significant effect on the financial performance of local governments. This implies that the higher the local own-source revenue, the better the financial performance of local governments, and the higher the economic growth, the greater the regional income that can optimize local revenue. Meanwhile, balance funds have a negative effect on the financial performance of local governments, meaning that the greater the transfer funds received from the central government, the higher the regional dependency, which leads to a decrease in financial performance.